2013
DOI: 10.1590/s0100-83582013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Fitossociologia de plantas daninhas do cafezal consorciado com leguminosas

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a fitossociologia de plantas daninhas em cafezais sob diferentes períodos de consórcio com leguminosas em dois anos de cultivo. Os tratamentos corresponderam à combinação fatorial entre as leguminosas feijão-de-porco (Canavalia ensiformis) e lablabe (Dolichos lab-lab) e períodos de consorciação com cafeeiros aos 30, 60, 90 e 120 dias após o plantio, mais uma testemunha sem leguminosa. O experimento foi composto por nove tratamentos em delineamento de blocos casuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Although D. horizontalis has completely disappeared from both areas, Brachiaria plantaginea was solely responsible for 75% and 52% of the Importance Value, respectively for the monocrop and intercrop systems; and G. coarctatum was also responsible for 47% of the Importance Value in the shaded, intercrop environment (Table 1). B. plantaginea occurs as a weed species in coffee plantations in Brazil (Moreira et al, 2013), demanding high light intensities for its emergence and development (Silva & Silva, 2007;Mondo et al, 2010).…”
Section: Phytosociologymentioning
confidence: 99%
“…Although D. horizontalis has completely disappeared from both areas, Brachiaria plantaginea was solely responsible for 75% and 52% of the Importance Value, respectively for the monocrop and intercrop systems; and G. coarctatum was also responsible for 47% of the Importance Value in the shaded, intercrop environment (Table 1). B. plantaginea occurs as a weed species in coffee plantations in Brazil (Moreira et al, 2013), demanding high light intensities for its emergence and development (Silva & Silva, 2007;Mondo et al, 2010).…”
Section: Phytosociologymentioning
confidence: 99%
“…The species of the genus Cyperus have a great competitive capacity, which can be found affecting different cultures, these weeds have wide adaptation, being found in all types of soil and climate, in addition, it has good dissemination with both sexual and asexual reproduction (Monquero, 2014). The importance of C. rotundus is even more evident as it is a kind of difficult chemical and/or mechanical control (Moreira et al, 2013) In the drip irrigated area, 27 of the 33 species identified were found throughout and all surveys, of these, highlighted the Amaranthus spp. and the E. hirta that were present in the field throughout the year with a greater number of individuals per species in all seasons.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kaspary (2014), in adult age, shoot dry mass of a single plant of the said species may reach 388.5 g, while total dry mass may be up to 494 g. In crop areas, S. latifolia may reach infestation of 350 plants m -2 (Acuña, 2000), a biomass of 23 g plant -1 (Costa et al, 2002) and up to 0.77 t ha -1 of dry matter (Gonçalves, 2015). P. phaseoloides, at a density of 0.69 plants m -2 , can accumulate up to 3.2 t ha -1 of shoot dry matter, while P. conjugatum, can accumulate up to 1.89 t ha -1 of dry matter in interrows in coffee growing areas (Moreira et al, 2013). Tables 3 and 4 show the total amounts of nutrients present in the leaves of orange plants and weeds and their relative content.…”
Section: Resultsmentioning
confidence: 99%